The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/wnr.0000000000000708
|View full text |Cite
|
Sign up to set email alerts
|

The activation of metabotropic glutamate 5 receptors in the rat ventral tegmental area increases dopamine extracellular levels

Abstract: The mesocorticolimbic circuit projects to the prefrontal cortex, hippocampus, amygdala, and nucleus accumbens, among others, and it originates in the dopaminergic neurons of the ventral tegmental area (VTA). The VTA receives glutamatergic inputs from the prefrontal cortex and several subcortical regions. The glutamate released activates dopaminergic neurons and its action depends on the activation of ionotropic and metabotropic glutamate receptors. VTA dopaminergic neurons release dopamine (DA) from axon termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…A possible mechanism is through blockage of mGlu5 in dopaminergic neurons in the ventral tegmental area (VTA). Ferrada et al (Ferrada et al 2017) reported that intra-VTA infusion of the selective mGlu5 agonist CHPG increased release of dopamine, suggesting the possibility that MPEP, acting at mGlu5 receptors in dopaminergic neurons in VTA, could reduce dopaminergic inputs to the striatum, counteracting the reduced corticostriatal glutamatergic inputs into striatum in DLX-mGlu5 KO mice, thus resulting in overall hypo-locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism is through blockage of mGlu5 in dopaminergic neurons in the ventral tegmental area (VTA). Ferrada et al (Ferrada et al 2017) reported that intra-VTA infusion of the selective mGlu5 agonist CHPG increased release of dopamine, suggesting the possibility that MPEP, acting at mGlu5 receptors in dopaminergic neurons in VTA, could reduce dopaminergic inputs to the striatum, counteracting the reduced corticostriatal glutamatergic inputs into striatum in DLX-mGlu5 KO mice, thus resulting in overall hypo-locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…Increased glutamate signaling may play a role in a tuning of the VTA, since activation of glutamate receptors modulates firing of dopaminergic neurons and regulates extracellular DA levels (Ferrada et al 2017;Floresco et al 2003;Lodge and Grace 2006;Oakman et al 1995).…”
Section: Vta and Snc Transcriptomes Respond Distinctly To Da Deficiencymentioning
confidence: 99%
“…GLU and GABA quantifications: experimental conditions were as described previously [ 28 , 29 ]. Briefly, 20 μL of each cleaned supernatant was mixed with 4 μL of borate buffer (pH 10.8), and then the mixture was derivatized by adding 4 μL of fluorogenic reagent (20 mg of orthophthaldehyde and 10 μL of β-mercaptoethanol in 5 mL of ethanol).…”
Section: Methodsmentioning
confidence: 99%